The Effectiveness of Genre Based Approach To Enhance The Speaking Performance of Junior High School Students At Sekolah Alam CEFA Kabupaten Kampar Riau Registered 2022/2023 Academic Years - Hendra Putra; Januarius Mujiyanto; Puji Astuti; Frimadhona Syafri (International Conference on Science, Education, and Technology, 2023)
English subject must be taught at Junior high High school level. One of English teaching material is procedure text. On Kurikulum Merdeka, an English teacher must master approach to teach English. One of approach to teach English subject on Kurikulum Merdeka is Genre Based Approach. The purpose of this study is to know the effectiveness of using Genre Based Approach for enhancing students speaking performance. This study uses quantitative approach with quasi experimental design . The total population is 22 students that consists of 12 students seventh grade as control group and 10 eighth grade students as experiemnt group. so the total sample is all of the students. This research has been conducted at Sekolah Alam CEFA Pekanbaru. To collect the data is used the test as an intrument. In anayzing data uses SPSS version 2.3 The result of this study found that genre based approach has significance effect toward students’ speaking performance. To mean score pre-test in treatment group is 36 and for control group is 74.It can be said that the average for pre-test is 55. Then it is included poor category. Meanwhile for post-test in control group is 74 and treatment group is 81. It can be summerized that after giving the treatment the individu score and mean score of the students in the beginning is low become higher that started from fail level into good level. This study is expected to utilize for the students, teacher and other researchers.